2008
DOI: 10.4049/jimmunol.180.7.4892
|View full text |Cite
|
Sign up to set email alerts
|

Relative Levels of M-CSF and GM-CSF Influence the Specific Generation of Macrophage Populations during Infection withMycobacterium tuberculosis

Abstract: Members of the CSF cytokine family play important roles in macrophage recruitment and activation. However, the role of M-CSF in pulmonary infection with Mycobacterium tuberculosis is not clear. In this study, we show the lungs of mice infected with M. tuberculosis displayed a progressive decrease in M-CSF in contrast to increasing levels of GM-CSF. Restoring pulmonary M-CSF levels during infection resulted in a significant decrease in the presence of foamy macrophages and increased expression of CCR7 and MHC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 27 publications
2
49
1
Order By: Relevance
“…Therefore, workers on many other respiratory diseases will clearly be able to use the approaches described here to elucidate the role of different molecules in pathogenesis (12,14). These same approaches may be exploited as immunotherapeutic alternatives for respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, workers on many other respiratory diseases will clearly be able to use the approaches described here to elucidate the role of different molecules in pathogenesis (12,14). These same approaches may be exploited as immunotherapeutic alternatives for respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate this, we describe, for the first time, the manipulation of target gene expression at a specific time during chronic pulmonary infection. Here, we have combine our recently published noninvasive local pulmonary therapy (12,14) with the recently developed technology of gene silencing mediated by siRNA (31)(32)(33)(34) to study the role of the pulmonary XCL1/lymphotactin chemokine during chronic infection with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these cytokines have been previously identified in the context of TB. For example, I-309 was shown to be upregulated in DC cells after TB-specific antigen stimulation (Jang et al, 2008;Yu et al, 2012) as were CXCL9 (MIG) (Bai et al, 2011), IL-10 (Hasan et al, 2011), IL-6 (Zhang et al, 1994, IL-7, IL-8 (Nakaya et al, 1995;Fietta et al, 2002;Boggaram et al, 2013;Huang et al, 2014), and G-CSF (Higgins et al, 2008). IL-10 is ananti-inflammatory molecule that mainly plays a negative role in immune regulation (Boussiotis et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF influences DC and macrophage recruitment into inflammatory sites, with transgenic overexpression of Csf2 in tumor cells eliciting DC recruitment in vivo (18). GM-CSF is also important for effective Ag processing and presenting function in APCs, with in vitro experiments showing that GM-CSF facilitates Ag uptake (19) and expression of MHC class II and the costimulatory molecules CD80 and CD86 (20)(21)(22), and this is linked with increased T cell activation (18,20,23,24) and T cell-dependent Ab production (25). Experiments in Csf2-null mutant mice have demonstrated that although macrophage and DC populations are essentially intact when GM-CSF is absent (26,27), this cytokine influences mature macrophage and DC function to affect the incidence and severity of some inflammatory and autoimmune diseases, including arthritis, multiple sclerosis, glomerulonephritis, and LPS-induced lung inflammation (28).…”
Section: Endritic Cells (Dcs) Have Emerged As a Critical Cell Lineagementioning
confidence: 99%